Integrative and sustainable port hinterland intermodal development with green concerns - Gu, Yimiao (2014)
Owing to a surge in international trade volume, greenhouse gas emissions are rapidly increasing. The challenge countries and societies face today is how to reduce the associated greenhouse gas emissions while the demand for transportation volume is growing. Sustainable development in the transportation domain deserves our utmost attention. An additional challenge comes from ever-increasing customer expectations and requirements, for example, door-to-door delivery and fast delivery at minimum cost. Through conducting an in-depth review of the literature concerning the container network optimisation domain and the environmental issues in transportation planning, it is found that very few efforts have been made to the issue of intermodal container flows considering both empty and laden containers with green concerns using bi-objective optimisation. This is a research gap which will be filled by this research. Considering all of the above, port hinterland intermodal development that addresses environmental concerns has become a crucial domain for exploration, which is the main objective of this research. Both qualitative and quantitative research methods are applied in this research. A qualitative research on comparing the potentials and challenges in terms of intermodal development in China and India is undertaken. Such a comparative analysis is useful for China and India while carrying out their port hinterland intermodal development. Other countries can also benefit from this research. Two original optimisation models are developed in this research as two quantitative research methods. The first model is a tactical model with green concerns incorporated as a constraint. The second model is an operational model that takes three environmental regulatory frameworks into consideration. This operational model adds to the literature by including in its investigation three environmental regulatory frameworks, namely: (1) carbon tax, (2) carbon emission trading scheme and (3) direct restriction on carbon emission.